Study on Overburden Rock Movement and Stress Distribution Characteristics under the Influence of a Normal Fault - Quansen Wu; Peng Kong; Quanlin Wu; Xinggang Xu; Xingyu Wu; Tao Guo (Advances in Civil Engineering)
Fault activation triggers local deformation and dislocation, releasing a large amount of energy that can easily cause mining disasters, such as rock bursts and roadway instability. To study the changing characteristics of overburden structures and the evolution law of mining-induced stress as panel advances towards a fault from a footwall, two similar models were established, namely, a simulation experimental model and a numerical simulation model. In addition, the relationship among mining, mining stress, and rock bursts induced by fault activation was investigated. The results of this study reveal that when the working face is 30 m away from the fault, the high-position rock mass near the fault turns to the goaf where the fault is activated, and the two walls display relatively obvious dislocation. During the process of footwall panel mining to the fault, the abutment stress of the coal pillar tends to increase initially, followed by a decrease. When the working face is 20 m away from the fault, the abutment stress ahead of the working face reaches its maximum. When the width of the coal pillar is within the range of 10–40 m, the coal pillar accumulates a large amount of energy, and the working face affected by the fault easily induces a rock burst. Before fault activation, disturbances arising from the mining activities destroy the equilibrium stress environment of the rock system surrounding the fault, and the fault continuously accumulates energy. When the accumulated energy reaches a certain threshold, under the action of normal stress or shear stress, the fault will be activated, and a large amount of energy will be released, which can easily induce a rock burst. The research results in this paper provide a scientific basis for the classification, prediction, and prevention of rock bursts under similar geological conditions.